Approaches to the analysis of production activity at archaeological sites - Hodgkinson, Anna K.; Tvetmarken, Cecilie Lelek, (Archaeopress Archaeology, 2020)
Proceedings of a workshop held in Berlin, 2018, focusing on manufacturing activities identified at archaeological sites. New excavation techniques, ethnographic research, archaeometric approaches, GIS, experimental archaeology, and theoretical issues associated with how researchers understand production in the past, are presented here.